Pengembangan Bahan Ajar Berbasis Rumus Pegon bagi Santri Tingkat Pemula di Pondok Pesantren Mambaul Ulum Banyuwangi - Abdul Latif; Evi Nurhalimah (Jurnal Tinta, 2026)
Learning the kitab kuning (classical Islamic texts) in Islamic boarding schools (pesantren), especially at the beginner level, often faces obstacles in understanding Arabic texts and writing pegon meanings, which require precision and relatively long time. This condition affects the low efficiency of learning and limits the space for deepening the material. This study aims to develop teaching materials based on Rumus Makna Pegon (Pegon Meaning Formulas) using the Research and Development (R&D) model with the ADDIE stages (Analysis, Design, Development, Implementation, Evaluation), and to analyze the effectiveness of the resulting product for beginner students (santri pemula) at the Manbaul Ulum Islamic Boarding School in Banyuwangi. Data were collected through observation, interviews, questionnaires, and documentation, then analyzed descriptively both qualitatively and quantitatively. The results show that the developed teaching materials are valid, practical, and effective in increasing students' speed and accuracy in writing meanings, helping systematic grammatical understanding, and supporting learning time efficiency. This study concludes that Rumus Makna Pegon is a relevant and applicable pedagogical innovation in learning kitab kuning in pesantren.